SEED QUANTITY ON IN VITRO CULTIVATION OF Dendrobium nobile LINDL. IN ALTERNATIVE CULTURE MEDIA WITHOUT SUBCULTURE - Soares, J. S.; Ribeiro, L. M.; Sorgato, J. C. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The in vitro orchid cultivation results in high percentages of germination when compared to the natural germination of these species, because their seeds have few or any nutritional reserves. The objective of this study was to evaluate different amounts of seeds in the in vitro propagation of Dendrobium nobile Lindl. var. nobilius and var. comet king in alternative medium, without subcultures. 0.02 g of seeds of each plant were used and disinfested in 0.8% sodium hypochlorite solution for 15 minutes, being diluted in sterile water until 60 mL was reached. In the aseptic environment, in vitro seeding was carried out 2, 3 or 4 mL of each seed suspension were pipetted into 600 mL glass vials provided with a metal stopper and containing 80 mL of the alternative culture medium. The cultures were transferred to the growth room with controlled temperature and photoperiod (25 ± 2 ºC, 16 hours) remaining for six months under these conditions. The highest number of potentially viable seeds (426 mg-1) was observed in D. nobile var. nobilius, while D. nobile var. comet king showed 164 mg-1 potentially viable seeds. The nobilius variety showed higher results in the total number of plants and live plants, number of leaves, number and diameter of pseudobulbs and length of the largest root, characteristic of this variety, which is more vigorous. The inoculation of 2mL was more efficient for the micropropagation of the two plants, with less competition between the seedlings in the flask.